-10
Пошаговое объяснение:
1/3(6а-18)-1/2(4b+8) = 1/3*3(2a-6)-1/2*2(2b+4) = (2а-6)-(2b+4) = 2а-6-2b-4 = 2а-10-2b
1/3(6а-18)-1/2(4b+8). a=3. b=3 [условие]
Разложим выражение на множители:
1/3*3(2a-6)-1/2*2(2b+4)
Сократим числа:
(2а-6)-(2b+4)
Сократим дробь, раскроем скобки:
2а-6-2b-4
И осталось вычислить:
2а-10-2b
-10
Пошаговое объяснение:
1/3(6а-18)-1/2(4b+8) = 1/3*3(2a-6)-1/2*2(2b+4) = (2а-6)-(2b+4) = 2а-6-2b-4 = 2а-10-2b
Пошаговое объяснение:
1/3(6а-18)-1/2(4b+8). a=3. b=3 [условие]
Разложим выражение на множители:
1/3*3(2a-6)-1/2*2(2b+4)
Сократим числа:
(2а-6)-(2b+4)
Сократим дробь, раскроем скобки:
2а-6-2b-4
И осталось вычислить:
2а-10-2b